Peran Guru Bimbingan dan Konseling Abad 21 dalam Meningkatkan Kemandirian Peserta Didik dalam Perencanaan Karier melalui Layanan Bimbingan Kelompok - Wadhlah, Zulfa Huwaidah; Rahmiawan, Natasya Artamefilla; Firdaus, Azzahro; Habsy, Bakhrudin All (Lembaga Yasin AlSys, 2024)
This study aims to explore and understand theoretically and philosophically about the role of guidance and counseling teachers in the 21st century through group guidance services that can increase independence in making career choices. We have used qualitative methods of literature study in conducting this research. Literature study is an integral part of research that involves gathering information and data by examining and evaluating theories contained in related literature. The results of our research are: (1) Conditions of High School Adolescents in Preparing for Careers (2) Level of Adolescent Awareness in Preparing for Careers (3) The Role of BK Teachers in Increasing Awareness of Career Planning (4) Century Progress in the Field of Career & Aspects of SKKPD (5) Group guidance services aspects of preparing for careers.